Stiffness Modulation in Flexible Rotational Triboelectric Nanogenerators for Dual Enhancement of Power and Reliability - Feng Li; Ao Yin; Yaao Zhou; Tao Liu; Qingqing Liu; Weijie Ruan; Ling Bu (Nanomaterials, 2024)
Rotational nanogenerators with flexible triboelectric layers have wide applications and high reliability. However, flexible materials cause a severe reduction in contact force and thus triboelectric output power. Unlike previous works devising complex auxiliary structures to solve this issue, this paper focuses on improving the contact material mechanics and proposes a stiffness modulation method. By introducing fine patterns to the contacting rotor–stator pairs, the effective elastic modulus was regulated from approximately 103 to 105 MPa, and the output voltage was modulated from approximately 24.39% to 375.87% compared to the non-patterned rotor–stator pairs, corresponding to a maximal a 14 times increase in output power. A maximal power density of 18.75 W/m2 was achieved on 10 MΩ resistance at 9.6 Hz, which is even beyond the power density of most rigid triboelectric interfaces. Moreover, high reliability could be maintained when the volume ratio of the horizontal patterns exceeded a threshold value of 33.5% as the stator and 63.6% as the rotor for a 0.5 mm linewidth. These results prove the efficacy of the stiffness modulation method for jointly achieving high output power and high reliability in flexible rotational triboelectric nanogenerators.